Prevalence of Intestinal Nematodes among Children below 10 years attending Kiwoko Hospital Pediatric Unit, Kasana, Nakaseke, District, Uganda. - Nvule, Henry Pecos (Student's Journal of Health Research Africa, 2021)
Background: Intestinal nematodes are among the most common parasites infecting humans in developing countries, precise estimates of the populations at risk of infection are difficult to derive. Therefore to understand the disease burden there is a need for reliable data on the prevalence of infection as well as information on the risk factors of infection. Methodology: 99 stool samples were collected from children who presented with diarrhea, fever, itchy anus opening all symptoms of intestinal nematode infection. Stool samples were screened using the direct saline method. Samples negative by direct saline were further examined using the formal ether technique and stained by eosin for visualization of parasites eggs. A questionnaire was administered to their guardians/parents to assess the risk factors of infection. Results: The prevalence of intestinal nematode infection was found to be 62.6% (62/99). The intestinal nematode infection rate was found to be higher in children over five years as compared to children below five years with a prevalence of 64.2% (43/67) and 59.4% (19/32) respectively. The prevalence of infection by sex was 66% (31/47) in males and 59.6% (31/52) in females. Ascaris lumbricoides were the most prevalent parasite identified in 25 of the 62 patients infected with intestinal nematodes. This was followed by Hookworm (17/62), Trichuris trichiura (12/62), and Strongyloides stercoralis(8/62). Poor hygiene was the most common risk factor cited followed by illiteracy and poverty. Conclusion and recommendations: The results show intestinal nematode infection is common in children attending the Kiwoko pediatric unit. This, therefore, calls for different stakeholders such as public health officers, medical personnel, and the community to develop new strategies to educate the community on existing government programs aimed at the elimination of intestinal nematode infection in children in the Nakaseke district.